EFEKTIVITAS PEMBELAJARAN JARAK JAUH MENGGUNAKAN LEARNING MANAGEMENT SYSTEM DI MASA PANDEMI COVID-19 - Astriani, Linda (Jurnal Holistika, 2021)
ABSTRACTDistance learning is carried out at all levels of education from elementary school to university during the covid-19 pandemic. Ecampus FIP UMJ is a web-based application for electronic learning activities. Ecampus FIP UMJ learning platform can be implemented remotely online. This study aims to analyze the effectiveness of learning using the LMS of the PGSD Study Program in the Early Elementary Elementary School Mathematics Education course. The participants in this study were 79 students in the second semester of the 2020/2021 academic year. Data collection using questionnaires. Data collection techniques used non-test data in the form of observation, questionnaires and documentation. The effectiveness questionnaire uses a Likert scale. The survey results showed that the average student response was 39.8% of students agreeing the ease of accessing the ecampus, 40.98% of students agreeing that understanding the material in learning uses ecampus, 40.5% of students agreeing that ecampus is effectively used in online learning, and 41, 8% of students agree to use ecampus in quizzes or exams for Early Elementary Mathematics Education courses. PJJ cannot 100% replace conventional learning (face to face) in the classroom but at least so that the wheels of education continue to spin and do not die completely paralyzed due to Covid-19.Keywords: Effectiveness, Distance Learning, LMS, Covid-19 Pandemic ABSTRAK Pembelajaran jarak jauh (PJJ) dilakukan pada semua jenjang pendidikan dari Sekolah Dasar sampai Perguruan Tinggi di masa pandemic covid-19. Ecampus fip umj merupakan aplikasi berbasis web untuk kegiatan pembelajaran elektronik (e-learning program). Platform ecampus fip umj pembelajaran bisa dilaksanakan dari jarak jauh secara online. Penelitian ini bertujuan untuk menganalisa efektivitas pembelajaran menggunakan LMS Program Studi PGSD pada mata kuliah Pendidikan Matematika SD Awal. Partisipan pada penelitian ini adalah mahasiswa semester 2 Tahun Ajaran 2020/2021 sebanyak 79 mahasiswa. Pengumpulan data yang menggunakan kuisioner. Teknik pengumpulan data menggunakan data non tes bentuk observasi, kuisioner dan dokumentasi. Angket efektivitas menggunakan skala likert. Hasil survey menunjukkan rata-rata respon mahasiswa terdapat 39,8% mahasiswa setuju kemudahan mengakses ecampus, 40,98% mahasiswa setuju jika pemahaman materi dalam pembelajaran menggunakan ecampus, 40,5% mahasiswa setuju jika ecampus efektiv digunakan dalam pembelajaran daring, dan 41,8% mahasiswa setuju dalam penggunaan ecampus dalam kuis atau ujian mata kuliah Pendidikan Matematika SD Awal. PJJ tidak bisa 100% menggantikan pembelajaran secara konvensional (tatap muka) di dalam kelas tapi setidaknya agar roda pendidikan terus berputar dan tidak mati total lumpuh karena Covid-19.Kata kunci: Efektivitas, Pembelajaran Jarak Jauh, LMS, Pandemi Covid-19